2021
DOI: 10.3389/fvets.2021.645076
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Transmission of Taenia solium Taeniasis/Cysticercosis in a Rural Area of Northern Rwanda

Abstract: Cysticercosis is a parasitic infection caused by the metacestode larval stage (cysticercus) of Taenia solium. In humans, cysticercosis may infect the central nervous system and cause neurocysticercosis, which is responsible for over 50,000 deaths per year worldwide and is the major cause of preventable epilepsy cases, especially in low-income countries. Cysticercosis infection is endemic in many less developed countries where poor hygiene conditions and free-range pig management favor their transmission. A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
(76 reference statements)
1
9
2
1
Order By: Relevance
“…The two domestic workers who were implicated as the source of infection in one Kuwaiti family showed no apparent signs of active infection (worm segments in stool samples) during treatment. However, this observation has also been noted in few other studies [4,13,56].…”
Section: Discussionsupporting
confidence: 66%
“…The two domestic workers who were implicated as the source of infection in one Kuwaiti family showed no apparent signs of active infection (worm segments in stool samples) during treatment. However, this observation has also been noted in few other studies [4,13,56].…”
Section: Discussionsupporting
confidence: 66%
“…Among studies based on copro Ag-ELISA conducted in Kenya, Rwanda, Tanzania, and Zambia, the highest prevalence was reported in Kenya at 19.7% [ 40 ]. Rwanda had a taeniosis prevalence of 1.4% [ 51 ], Tanzania ranged between 0.5 to 5.2% [ 55 , 72 ] [ 16 ], [ 22 ] and Zambia ranged between 0.3 to 13.8% [ 62 , 73 ] ( Fig 10 ). For details on sources refer to Table 6 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, malaria prevalence in Rwanda ranges from 17% in the East, 11% in the South to 1% in the North [48]. Further, a Northern Rwandan study documented a Taenia solium seropositivity in children of 13.3% [49], while a Southern study reported a general seropositivity of 18.4% with almost…”
Section: Discussionmentioning
confidence: 99%
“…For instance, malaria prevalence in Rwanda ranges from 17% in the East, 11% in the South to 1% in the North [48]. Further, a Northern Rwandan study documented a Taenia solium seropositivity in children of 13.3% [49], while a Southern study reported a general seropositivity of 18.4% with almost a quarter of PwE considered as neurocysticercosis cases [50]. The clustering of risk factors is particularly evident given the higher prevalence in rural areas where factors such as poor perinatal care, poor sanitary conditions with higher transmission rates of infections, and poverty are all pervasive [2, 4].…”
Section: Discussionmentioning
confidence: 99%